HUBUNGAN ANTARA PENGELOLAAN SEKOLAH, IKLIM SEKOLAH, DAN PARTISIPASI MASYARAKAT DALAM MENINGKATKAN MUTU SEKOLAH DENGAN EFEKTIVITAS SEKOLAH DI PROVINSI JAWA TIMUR - Sediono Abdullah (Universitas Negeri Jakarta, 2010)
The objective of this research is to get information on the relationships among school management, school climate, and community participation in improving educational quality toward school effectiveness at schools which received Piloting School Based Management Program.The research was conducted at the schools in Probolinggo district, East Java Province with n = 100, selected randomly.The research concludes that there is positive correlation between: (1) school management and school effectiveness; (2) school climate and school effectiveness; (3) community participation in improving educational quality and school effectiveness. Furthermore, there is positive correlation between those three independent variables with school effectiveness.Therefore school effectiveness could be improved by enhancing school management, school climate and community participation in improving educational quality.